Actuación directa de personas naturales o jurídicas en procesos aduaneros de comercio exterior sin intervención de agencias de aduanas (2022)
The great complexity with which trade operations are carried out today, has obliged to all commercial actors and national and international agents, not only from Colombia but the entire world, to establish guidelines to control and limit certain actions. Imports, exports and customs transits were until about 20 years ago in Colombia, subject to the services offered by customs agencies and customs agents, which implied that no process or operation could be carried out without their intervention. In Colombian regulations, customs agents appear as auxiliary organizations and collaborators of the Colombian Tax and Customs Directorate. Its main purpose is the strict application of the current customs regime of the parties involved in a foreign trade operation (importers, exporters) guaranteeing the prevention of crimes such as money laundering, drug trafficking, financing of terrorism and evasion of taxes among other typified crimes. With decree 1165 of 2019 in its article 33, the national government authorizes natural and/or legal persons in its name and representation to carry out the customs procedures that are in place to carry out the operations of foreign trade before the customs authority without the intermediation of a customs agency, defined there in summary as Direct Declarant. In the present investigation process, it is intended to determine what are the actions legal and obligatory that natural and legal persons can carry out in the development of the export and import business operations themselves, all the specific processes that involving foreign trade operations and natural and legal persons, are intended to be evaluated in the development of this investigative process, not without leaving aside the benefits, advantages and disadvantages that this decision of the national government entails, the impact that in the 8importer and in the union of customs agencies generates in importers and all those costs, economic, political, and social factors and consequences that are related to external business operations. Regarding customs agencies, here an analysis will be presented on what are the affected (level II, III and I) whose main market niche is small and medium-sized companies with lower imports in FOB value, frequency and quantity. Without However, rather than analyzing or presenting previous results, evidence, or research on how Some operations may affect the structure of natural or legal companies, which is will present is the analysis of the causes and consequences of the same.